2008
DOI: 10.1080/14330237.2008.10820171
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Social Well-Being in a Motor Manufacturing Organisation in South Africa

Abstract: he study examined the psychometric properties of the 15-item version of the Social Well-being Scale (SWBS-15: Keyes, 1998) for a South African sample with diversity in culture. The SWBS-15 and a biographical questionnaire were administered to employees in a motor manufacturing organisation (N = 203). The five-factor structure of social well-being obtained previously in Western studies, were not replicated. Instead, we found three factors with acceptable levels of internal consistency emerged through explorator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…The present study expands the research conducted by De Jager et al (2008), amongst others, through applying CFA and ESEM to investigate the factor structure of the social wellbeing measure in an African sample. As indicated by Lages et al (2018, p.16) 'a proper understanding of mental health derives from the existence of valid and reliable measurement instruments, theoretically driven and adapted to their application contexts'.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…The present study expands the research conducted by De Jager et al (2008), amongst others, through applying CFA and ESEM to investigate the factor structure of the social wellbeing measure in an African sample. As indicated by Lages et al (2018, p.16) 'a proper understanding of mental health derives from the existence of valid and reliable measurement instruments, theoretically driven and adapted to their application contexts'.…”
Section: Introductionmentioning
confidence: 72%
“…A South African study utilising the 15-item short-form version found an emic factor structure comprising three dimensions amongst a sample of employees in a motor manufacturing sector (De Jager et al, 2008). Notwithstanding that De Jager et al (2008) could not replicate Keyes' (1998) theoretically intended model, their interpretation of the factor solution was contextually meaningful and useful for our exploration.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, as social well-being is multidimensional, we also noted that at least one of its five dimensions, namely social acceptance, was found to be significantly lower among younger age groups (18-29 and 30-44 groups) compared with the 60+ age group. This finding suggests that the link between age and social well-being remains equivocal and inconclusive (de Jager, Coetzee, & Visser, 2008) and should be seen in the context of Keyes' (1998) initial observation that social well-being is heterogeneous across ages. In contrast, consistent with previous findings (e.g., Keyes, 1998;Zhang, Chen, McCubbin, McCubbin, & Foley, 2011), social well-being was found to be positively associated with education and income.…”
Section: Discussionmentioning
confidence: 88%